2020
DOI: 10.1111/jpn.13459
|View full text |Cite
|
Sign up to set email alerts
|

Growth, behavioural, serum biochemical and morphological changes in female rabbits fed high‐fat diet

Abstract: This study aimed to determine whether high‐fat diet (HFD) could cause growth, behavioural, biochemical and morphological changes in young female rabbits. Thirty‐six female rabbits were randomly divided into two groups fed with either a high‐fat diet (HFD) or a standard normal diet (SND) for 5 weeks. Growth and behavioural changes were recorded during the 5‐week feeding period. Tissue samples, including blood and adipose tissue, were obtained after slaughter. HFD rabbits weighed more by the end of the feeding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
(42 reference statements)
2
16
1
Order By: Relevance
“…Anatomical phenotypic differences ( Supplementary Figure S1 ) showed that rabbits fed a high–fat diet contained large amounts of fat under the skin and on the viscera, which was consistent with previous studies, indicating that the high–fat diet achieved the expected obesity effect [ 17 ]. Small RNA from skeletal muscles of rabbits in CON–G and HFD–G were sequenced with a HiSeq 2500 (SE50) sequencer.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Anatomical phenotypic differences ( Supplementary Figure S1 ) showed that rabbits fed a high–fat diet contained large amounts of fat under the skin and on the viscera, which was consistent with previous studies, indicating that the high–fat diet achieved the expected obesity effect [ 17 ]. Small RNA from skeletal muscles of rabbits in CON–G and HFD–G were sequenced with a HiSeq 2500 (SE50) sequencer.…”
Section: Resultssupporting
confidence: 89%
“…Rabbits in both groups were fed from 35 to 70 days of age. The methods in this study were based on our previous research [ 17 ], which indicated that body weight at 70 days of age (2–2.5 kg) is an important reference index to evaluate obesity in rabbits under the same feeding conditions. In this study, 3 rabbits with the highest body weight in each group were screened out before all of the rabbits were killed by intravenous injection.…”
Section: Methodsmentioning
confidence: 99%
“…Before each stage, rabbits were housed undisturbed for 7 days to adapt to the change. Animals were classified as obese using the method described in our previous study [ 11 ]. Briefly, body weight, body length, bust length, and adipose tissue weight were used as the markers of obesity.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the study, weak (rabbits kept away from the feed and did not eat continuously for more than 2 days), disabled (rabbits with obvious limb deformities), and sick (rabbits with significant skin diseases) rabbits were eliminated. Rabbits were classified as obese using the method described in our previous study [ 16 ]. Briefly, body weight, body weight gain, and BMI were measured as markers of obesity.…”
Section: Methodsmentioning
confidence: 99%